Pengaruh Kinerja Keuangan terhadap Harga Saham pada Emiten Jakarta Islamic Index - rohman, Ahmad maza; Syarofi, Muhammad; M. Salmanidou, Dimitra (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2025)
This study aims to evaluate the extent to which financial performance affects stock prices of companies listed in the Jakarta Islamic Index (JII), contributing to the enhancement of awareness and participation in sharia-compliant investments. The research adopts a quantitative approach using a survey method and falls under the category of explanatory research. All issuers consistently listed in the JII during the observation period were selected as samples using a saturated sampling technique. Data analysis was conducted through multiple linear regression, with hypothesis testing using the t-test and coefficient of determination (R²) to measure the strength of influence. The findings reveal that financial performance has a significant impact on stock prices, as indicated by a t-value of 10.339, which exceeds the critical value of 1.729, and a significance level of 0.000, below the threshold of 0.05. The R² value of 0.939 implies that 93.9% of the variation in stock prices can be explained by financial performance. These results support the signaling theory and efficient market hypothesis, which suggest that a company's financial information directly influences investor decisions. Therefore, improving financial transparency and enhancing sharia financial literacy are essential to promote a sustainable and inclusive Islamic capital market.